2022
DOI: 10.1177/15353702221121631
|View full text |Cite
|
Sign up to set email alerts
|

Polyadenylate-binding protein cytoplasmic 1 mediates alternative splicing events of immune-related genes in gastric cancer cells

Abstract: Polyadenylate-binding protein cytoplasmic 1 (PABPC1) is dysregulated in malignancies, which is considered as a potential therapeutic target for many cancer types. By alternative splicing (AS) for gastric cancer (GC), we described PABPC1-modulated AS events in this study. PABPC1 expression was analyzed in 408 GC tissues from The Cancer Genome Altas (TCGA) database. Human gastric adenocarcinoma (AGS) cells were transfected with PABPC1-specific small interfering RNA (siPABPC1) with siCtrl as a negative control. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The biological effects of PABPC1 expression in major translation zone aggregation, which can enter the nucleus under biological stress 30 . Currently, the role of PABPC1 expression is primarily researched in cancer, neurodegenerative diseases, cardiovascular diseases, and spermatogenesis disorders 12,31 . Chorghade et al demonstrated that the specific upregulation of PABPC1 in cardiomyocytes could trigger protein synthesis and physiological myocardial hypertrophy 32 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The biological effects of PABPC1 expression in major translation zone aggregation, which can enter the nucleus under biological stress 30 . Currently, the role of PABPC1 expression is primarily researched in cancer, neurodegenerative diseases, cardiovascular diseases, and spermatogenesis disorders 12,31 . Chorghade et al demonstrated that the specific upregulation of PABPC1 in cardiomyocytes could trigger protein synthesis and physiological myocardial hypertrophy 32 .…”
Section: Discussionmentioning
confidence: 99%
“… 30 Currently, the role of PABPC1 expression is primarily researched in cancer, neurodegenerative diseases, cardiovascular diseases, and spermatogenesis disorders. 12 , 31 Chorghade et al demonstrated that the specific upregulation of PABPC1 in cardiomyocytes could trigger protein synthesis and physiological myocardial hypertrophy. 32 Additionally, the inhibition of PABPC1 expression has been certified to influence the replication of Listeria monocytogenes , thus better modulating inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations